1989
DOI: 10.1677/joe.0.1200231
|View full text |Cite
|
Sign up to set email alerts
|

An acid-stable insulin-like growth factor (IGF)-binding protein from pig serum inhibits binding of IGF-I and IGF-II to vascular endothelial cells

Abstract: The effects of a porcine insulin-like growth factor (IGF)-binding protein on binding of IGF-I and IGF-II to porcine aortic endothelial cells (PAEC) were determined. Binding of 125I-labelled IGF-I and -II to IGF receptors was inhibited by IGF-binding protein. IGF-binding protein inhibited binding of IGF-I and -II in a dose-dependent manner with half-maximal inhibition occurring at 5.43 and 108 micrograms/l respectively. A 125I-labelled IGF-I--IGF-binding protein complex, formed by incubating 125I-labelled IGF-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The inhibitory action of soluble IGFBP-2 on ligand-receptor interaction and IGF-induced DNA synthesis in NSCLC cell line MOR is consistent with the contention that secreted/exogenous IGFBPs can act as blocking agents preventing IGF association with cell surface receptors. Similar observations have been made for IGFBP-1 and IGFBP-3 which block the cell surface association of radiolabeled IGF-I and which can inhibit either cell proliferation and/or cell function in a variety of different cell types (21)(22)(23)(24).…”
supporting
confidence: 74%
“…The inhibitory action of soluble IGFBP-2 on ligand-receptor interaction and IGF-induced DNA synthesis in NSCLC cell line MOR is consistent with the contention that secreted/exogenous IGFBPs can act as blocking agents preventing IGF association with cell surface receptors. Similar observations have been made for IGFBP-1 and IGFBP-3 which block the cell surface association of radiolabeled IGF-I and which can inhibit either cell proliferation and/or cell function in a variety of different cell types (21)(22)(23)(24).…”
supporting
confidence: 74%
“…It must also be considered that the IGFAGFBP-3 complex may not produce the same response in all cell types. Previous results in other systems indicate that formation of this complex can enhance or reduce IGF activity in a cell type-dependent manner (Blum et al, 1989;Ernst and Rodan, 1990;Conover and Powell, 1991;Gopinath et al, 1989;Bicsak et al, 1990;De Mellow and Baxter, 1988).…”
Section: Igf Regulation Of Igfbp-3 Levelsmentioning
confidence: 94%
“…IGFBPs are secreted proteins that are known to modulate the activity of IGFs. Depending upon the system, IGFBPs can increase or decrease the activity of IGFs (Blum et al, 1989;Ernst and Rodan, 1990;Conover and Powell, 1991;Gopinath et al, 1989;Bicsak et al, 1990 De Mellow andBaxter, 1988). In ectocervical epithelial cells IGFBP-3 inhibits the mitogenic effects of IGF1, presumably by forming a complex with and preventing IGFl from interacting with the transmembrane type I IGFl receptor (i.e., lowering the concentration of free IGF in the extracellular environment) (Andreatta-van Leyen et al, 1994;Hembree et al, 1994).…”
Section: Igf Regulation Of Igfbp-3 Levelsmentioning
confidence: 99%
“…Some IGFBPs may occur as phosphorylated or non-phosphorylated forms [lo]. It has been suggested that, according to their type or form, the IGFBPs can stimulate or inhibit the actions of IGFs by interfering with their binding to IGF receptors [ 11,121. It is therefore generally believed that the production of IGFBPs by cancer cells is of great importance and controls the regulation of cell proliferation, and of tumor growth, by the IGFs and the IGF-I receptor [8].…”
mentioning
confidence: 99%